2014
DOI: 10.1093/hmg/ddu151
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble tumor necrosis factor is therapeutic in Huntington's disease

Abstract: Neuroinflammation is a common feature of many neurodegenerative diseases, including Huntington's disease (HD). HD is an autosomal dominant genetic disease caused by an expanded CAG repeat in exon 1 of the huntingtin (HTT) gene. Previous studies demonstrated that levels of several proinflammatory cytokines, including tumor necrosis factor (TNF)-α, were higher in the plasma and brain tissues of mice and patients with HD, suggesting that inflammation may contribute to HD progression. To evaluate the pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 63 publications
6
71
1
Order By: Relevance
“…In addition to altered chemokine profiles, there is considerable evidence that demonstrates increased levels of circulating and CNS-borne pro-inflammatory cytokines, including IL-6, IL-8, and TNF-α (147). Reinforcing the potential importance of TNF-α in HD pathogenesis, it has recently been shown that therapeutic inhibition of TNF-α activity can significantly attenuate central and peripheral inflammation in the R6/2 HD model mice (149). …”
Section: Huntington’s Diseasementioning
confidence: 99%
“…In addition to altered chemokine profiles, there is considerable evidence that demonstrates increased levels of circulating and CNS-borne pro-inflammatory cytokines, including IL-6, IL-8, and TNF-α (147). Reinforcing the potential importance of TNF-α in HD pathogenesis, it has recently been shown that therapeutic inhibition of TNF-α activity can significantly attenuate central and peripheral inflammation in the R6/2 HD model mice (149). …”
Section: Huntington’s Diseasementioning
confidence: 99%
“…R6/2 astrocytes also produced more damage on primary R6/2 neurons in comparison to control astrocytes during inflammation in vitro . The role of TNFα in HD pathogenesis was examined using the dominant negative inhibitor XPro1595 [82]. XPro1595 is a selective inhibitor of soluble TNFα that interferes with its binding to TNFα receptors.…”
Section: The Role Of Astrocytes In Hd Neuroinflammationmentioning
confidence: 99%
“…Moreover, XPro1595 protected the cytokine-induced toxicity in both in vitro models. In vivo , XPro1595 decreased TNF- α levels in the cortex and striatum, improved motor function, reduced caspase activation, diminished the amount of mutant HTT aggregates, increased neuronal density, and decreased gliosis in the brain of R6/2 mice [58]. …”
Section: Anti-inflammatory Drugs For the Treatment Of Hdmentioning
confidence: 99%